MAIYAH MOCOPAT SYAFAAT DALAM PERSPEKTIF PSIKOLOGI - Muhammad Azizul Mustafa (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Abstract: This article describes the mocopat Maiyah Intercession in Psychology perspective. Psychology viewpoint in this article from the perspective of the four major schools of psychology, namely: Psychoanalytic, Behavioristik, Humanistic and Transpersonal. Maiyah mocopat Intercession is a panel of scientific study that is a discussion (sinau together) or sharing on topics of humanity, which teaches the spirit of living with tolerance and live together in kindness contribution. Maiyah which means "togetherness" in the first sense: together everyone always with God. Secondly: wherever they are always with God. Third: do whatever it is always with God. Fourth: under any circumstances just be with God. In berMaiyah there are many grains of knowledge to be gained. Because of something that is considered good by someone not necessarily good for other people, then what happens in Maiyah not a pendoktrinan ideology, nor is it an authoritarian system, do not rely on one figure, but work together to find the truth of science, in other words, not looking for anyone true, but look for what is right. The truth that they will each take their own tests in their own lives. In the perspective of psychology, the basic assumption emha ainun nadjib figure can be analogized as a psychologist as well as other sources and pilgrims Maiyah is a participant. In the process, activity which was attended by a variety of people from different interdisciplinary backgrounds vary, making the research to get information are diverse, there are people who come to the enlightened life (curative) through counsel of spiritual and moral message will be full of wisdom values, there are set out to align the map of life (preventive) in the frame or in new ways, and those who set out to develop a level of insight into life (development) in memanagement memanagement self and external reality. In Psychoanalytic perspective Maiyah activity is seen as a form of how his attitude towards the reality of life (ego), how menjinakkkan human desires are not tertarah (id) to remain in the course of (superego). Behavior viewed from the standpoint of pilgrims Maiyah behaviors that tend to gather together transmit sciences with each other. In the Humanist perspective view of human nature to always seek the truth and make themselves as "human freedom" for all the problems of life. Transpersonal Perspective're looking at that berMaiyah means: a person's tendency to anytime, anywhere, by anyone and in any case, always be a "man", which constantly unite yourself with the Divine (Ma`iyatullah).